Large gap two dimensional topological insulators: the bilayer triangular lattice TlM (M = N, P, As, Sb). Issue 17 (13th April 2017) - Zhou, Pan; Xue, Lin; Sun, Lizhong
Abstract : Based on density functional theory and Berry curvature calculations, we predict that the p–p band inversion type quantum spin Hall effect (QSHE) can be realized in a series of two dimensional (2D) bilayer honeycomb TlMs (M = N, P, As, Sb), which can be effectively equivalent to a bilayer triangular lattice for low energy electrons. Abstract : Based on density functional theory and Berry curvature calculations, we predict that the p–p band inversion type quantum spin Hall effect (QSHE) can be realized in a series of two dimensional (2D) bilayer honeycomb TlMs (M = N, P, As, Sb), which can be effectively equivalent to a bilayer triangular lattice for low energy electrons. Further topological analysis reveals that the band inversion between p− z and p x, y of the M atom contributes to the non-trivial topological nature of TlM. The band inversion is independent of spin–orbit coupling which is distinctive from conventional topological insulators (TIs). A tight binding model based on a triangular lattice is constructed to describe the QSH states in the systems. Besides the interesting 2D triangular lattice p–p type inversion for the topological mechanism, the maximal 550 meV local band gap (TlSb) and the tunable global band gap of the systems provide a new choice for a future room temperature quantum spin Hall insulator (QSHI). Considering the advance of the technology of van der Waals passivation, combination with hexagonal materials, such as h-BN, enables TlMs to show great potential for future 2D topological electronic devices.